Positive Classification Advantage: Tracing the Time Course Based on Brain Oscillation - Yan, Tianyi; Dong, Xiaonan; Mu, Nan; Liu, Tiantian; Chen, Duanduan; Deng, Li; Wang, Changming; Zhao, Lun (Frontiers in Human Neuroscience, 2018)
The present study aimed to explore the modulation of frequency bands (alpha, beta, theta) underlying the positive facial expressions classification advantage within different post-stimulus time intervals (100–200 ms, 200–300 ms, 300–400 ms). For this purpose, we recorded EEG activity during an emotion discrimination task for happy, sad and neutral faces. The correlation between the non-phase-locked power of frequency bands and reaction time (RTs) was assessed. The results revealed that beta played a major role in positive classification advantage (PCA) within the 100–200 and 300–400 ms intervals, whereas theta was important within the 200–300 ms interval. We propose that the beta band modulated the neutral and emotional face classification process, and that the theta band modulated for happy and sad face classification.